1998
DOI: 10.2118/98-04-03
|View full text |Cite
|
Sign up to set email alerts
|

Oil Recovery From Tarmat Reservoirs Using Hot Water And Solvent Flooding

Abstract: The existence of tar accumulations (tarmat) beneath the oil zone in some reservoirs creates productivity problems through restricted aquifer support during the primary recovery stage. It also affects the performance of peripheral water injection when the tar/oil boundary is irregular. The objective of this study was to investigate and evaluate combined solvent and hot water injection beneath the tarmat to improve aquifer support by displacing and dispersing the tar. Displacement runs were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…On the other hand, after adding additives such as clay minerals or metallic additives which have a catalytic effect on crude oil combustion reactions, the activation energies will generally decrease around 30%~70% in the HTO stage, while no obvious effects on the LTO stage were observed. Fig 7 below shows the activation energy distribution of crude oil with the presence of additives which includes 25 cases [6,10,15,18,33,34,35,[48][49][50][51][52][53][54].…”
Section: Presence Of Additives Effectmentioning
confidence: 99%
“…On the other hand, after adding additives such as clay minerals or metallic additives which have a catalytic effect on crude oil combustion reactions, the activation energies will generally decrease around 30%~70% in the HTO stage, while no obvious effects on the LTO stage were observed. Fig 7 below shows the activation energy distribution of crude oil with the presence of additives which includes 25 cases [6,10,15,18,33,34,35,[48][49][50][51][52][53][54].…”
Section: Presence Of Additives Effectmentioning
confidence: 99%
“…Particularly, thermal EOR implemented in many projects such as steam stimulation, or cyclic steam flooding, also known as steam flooding, Steam Assisted Gravity Drainage (SAGD) and hot water injection (Teodoriu et al 2007;Alajmi et al, 2009). Many authors in both laboratory experiments and numerical simulation have shown that the oil viscosity and mobility ratio can be reduced by hot water injection, ultimately resulting in improved oil recovery (Teodoriu et al, 2007;Taber, 1998;Milton et al, 2003;Prats, 1982;Goodyear et al, 1996;Bousaid, 1991;Jabbour et al, 1996;Okasha et al, 1998;Alajmi et al, 2009). Martin et al (1968) reported a case study that the hot water flooding yield oil recovery increasing for a pilot test in the Loco field in southern Oklahoma.…”
Section: Introductionmentioning
confidence: 99%
“…These optimum sizes for reformate and naphtha were 9.45 and 10.93% total hydrocarbon pore volume (THPV), respectively. Solvent slugs that are larger or smaller than this optimum size are less effective [12]. Another study was conducted by Harouaka and Asar [13] on tar properties and methods for improving injectivity in tarmats using naphtha and steam.…”
Section: Introductionmentioning
confidence: 99%